Determination Ofapoptosis Inducing Active Principles in Chosen Marine Sponges - Joseph, Vinod; Kavimani, S. (Asian Journal of Pharmaceutical Research and Development, 2015)
Secondary or primary metabolites produced by marine organisms may be potential bioactive compounds of interest in the pharmaceutical industry. Marine organisms exhibit a wide range of biological activities like anti-fertility, antiviral, antibiotic, antifungal and antimicrobial activities. In this study an attempt has been made to purify and partially characterize the active metabolites of the metabolic extract of the marine sponges, Sigmadocia carnosa and Clathria gorgonoides, which showed more potency in the pharmacological studies. The sponge Sigmadocia carnosa has showed rich source for several bis-1-oxaquinolizidine alkaloids, exhibiting diverse biological properties such as cytotoxic, antifungal, antimalarial, anti-tuberculosis and anti-rat brain nitric oxide synthase activities (Venkateswarlu et al., 2004; Rao et al., 2004). It was also evident that the efficacy of methanolic sponge extracts has been reduced in the lower temperature. The GC MS analysis of Sigmadocia carnosa showed that it contains around 10 compounds. The two major peaks at retention time 5.85 and 7.26 are identified as Iodophenyl (19.28 %) and Ephedrine (51.85 %). In conclusion, Sigmadocia carnosa offers a valuable candidate lead compound to counter growing drug resistance in cancers.